The association between school compliance towards Whole-School Environmental Mapping Framework and weight status of school children: a preliminary study - Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Aryati, Ahmad; Rasyidah, G (2015)
There is evidence to suggest that the school environment has significant contributions to the rising of childhood obesity. The objective of this study therefore to examine the association between school compliance toward “Whole-School Environmental Mapping Framework” (physical, economic, political and socio-cultural) with weight status of school children in Terengganu. The study design was a cross-sectional study. A total of 10 schools were randomly selected (4 urban and 6 rural in Kuala Terengganu and 20 teachers have been interviewed face to face by using a set of validated Malay version “Whole-school Environmental Mapping” questionnaire. Twenty-five children aged 10 and 11 years were randomly selected from each school in which their weight and height were measured to calculate body mass index (BMI). BMI was defined using WHO 2007 reference chart. This study has demonstrated that non-compliance schools (n = 8) have significantly higher proportion of obese children compared to schools that comply (n = 2) with the “WholeSchool Environmental Mapping Framework”. As a conclusion, this study has produced evidence that the school environmental factors may contribute to the higher prevalence of childhood obesity. Advanced improvement needs to be highlighted since the level of compliance towards the school environmental mapping is very low while the prevalence of obesity is high.